O efeito da temperatura de queima no agregado sintético de argila calcinada, aplicado em concreto asfáltico - (:unkn) unknown (Universidade Federal do Amazonas, 2008)
The Amazon Region presents high costs concerning pavement services, mainly because of its petro-material lack, that occurs with pebbles or river gravel which are distant from the consumption location. The frequently used coarse aggregate in this region is the river gravel, taken from the river bed, with an at least 450 km distance from the great consumption centers, resulting in a high transportation fee approaching 50% of its final product cost. Searching for an alternative and non-conventional material which could replace the river gravel or the pebble, the clay was studied due to its mineral abundance in the Amazon region. The utilized clay in this study is from floodplain areas located in the city of Manacapuru, in the State of Amazonas.The productive process adopted by the ceramic industry was reproduced in laboratory tests, in a manually and crafty, evidently. In order to accomplish the tests, a mill composed by 3 mobilesquare mouthpieces with dimensions of 12,7 mm, 9,5 mm and 4,8 mm was utilized. Part of the 4,8 mm fraction produced aggregate was triturated in order to obtain a 2,0 mm fraction. The produced aggregate were calcinated at 780º, 850ºC, 950ºC, 1050ºC and 1150ºC, and characterized according to the post-boiling loss of mass, absorption, specific mass, detritions by Los Angeles abrasion, bituminous alloy adhesiveness, chemical analysis, and mineralogical electronic microscopic sweeping. The calcinated aggregate at 850ºC, 950ºC, 1050ºC and 1150ºC were applied in asphaltic concrete, enframed in the C zone of DNIT. A comparative analysis between the conventional CBUQ (river gravel CBUQ) and the synthetic aggregate was made, which the analyzed parameters were stability, fluency, traction resistance by diametric compression and resilient modulus. The results portrayed that the resultant aggregate from the 780ºC calcinations showed itself more absorptive than the others. The confectioned CBUQ with the 850ºC calcinated aggregate, needed more alloy than the confectioned CBUQ’s with river gravel or other synthetic aggregates in different temperatures. Also, it was observed that the temperature increasing resulted in a real specific mass reduction of the aggregate, due to the existence of expansive elements in the specimen analyzed. The results also showed that all the mixtures confectioned with synthetic aggregate presented more stability compared to the conventional mixture, becoming technically viable for this region, the construction of asphaltic revetments with these aggregates.
Keywords: Synthetic aggregate; Calcinated clay; Asphaltic concrete; Burning temperature; Agregado sintético; Argila calcinada; Concreto asfáltico; Temperatura de queima; ENGENHARIAS: ENGENHARIA CIVIL